Conceptualisation of miss hominum as an expression of imago Dei: from missio Dei to missio hominum - Thinane, Jonas (AOSIS, 2022)
Academic data show little evidence that the concept of the missio hominum was ever explored beyond its context as developed by Nico Smith. There is little to no research that has conceptualised this phenomenon in light of imago Dei and the role it should play in fulfilling missio Dei’s mandate. It uses the relational nature of the Union of the Divine Trinity derived in imago Dei to conceptualise the idea of the missio hominum in the broader context of missio Dei. It aims to examine the role of missio hominum in fulfilling the objectives and scope of missio Dei. Missio Dei here means the mission of God, which uses human relationships as an instrument to achieve the eternal goal of missio Dei. Nico Smith’s account is used here to support the need for missio hominum within the broader understanding of missio Dei. This research is a first step towards a deeper understanding of the missio hominum in service to missio Christos and missio spiritus and the collective participation of missio ecclesiae towards the goal of missio Dei. The academic focus on missio hominum from Smith’s perspective is lacking or neglected by missiology scholars.
Keywords: Missio Dei; Missio Christio; Missio spiritus; Missio hominum; Imago Dei